Cognitive behavioral therapy for pediatric obsessive-compulsive disorder delivered via internet videoconferencing: a manualized sensor-assisted feasibility approach - Klein, Carolin S.; Alt, Annika K.; Pascher, Anja; Kühnhausen, Jan; Seizer, Lennart; Ilg, Winfried; Thierfelder, Annika; Primbs, Jonas; Menth, Michael; Barth, Gottfried M.; Gawrilow, Caterina; Conzelmann, Annette; et al. (Child and Adolescent Psychiatry and Mental Health, 2024)
Background: Between 1 and 4% of children and adolescents suffer from obsessive-compulsive disorder (OCD) worldwide, but the majority of these young people do not have access to cognitive behavioral therapy (CBT) as a first-line treatment. CBT delivered via online videoconferencing (vCBT) offers a new way to provide young people with therapy, especially in the home environment where symptoms usually occur. Methods: In this study, we investigated the feasibility of a newly revised vCBT manual, symptom change during treatment, and effects on family life and social functioning. 20 patients with OCD, aged 12–18 years, were treated during 14 weekly sessions while using a multimodal sensor system that assessed their physiological and behavioral responses during therapy. Treatment was delivered in real time via an online videoconferencing platform. Measurements of feasibility, acceptance, and implementation were evaluated descriptively, and clinical measures were assessed with t tests. Results: The primary results showed that patients and parents perceived the manual-based vCBT as feasible and easy to understand. According to the therapists’ ratings, all treatment modules and the content could be carried out in accordance with the manual. As a secondary outcome, OCD symptoms improved significantly during treatment (p <.001, d = 1.87), revealed by an average decrease of more than half in the Children’s Yale-Brown Obsessive-Compulsive Scale (CY-BOCS) score. As the psychotherapy could be implemented directly in the patients’ home environment, low barriers to participation were reported, and the majority of participants reported improvements in family life after treatment. Conclusions: In summary, the results of this feasibility study indicated a successful application of manual-based psychotherapy delivered via videoconferencing for pediatric OCD supported by a sensor system. This method should be further investigated in future randomized controlled trials with larger patient samples. Clinical trial registration: [www.ClinicalTrials.gov], identifier [NCT05291611], first submission: 2021-12-10.
Created from Fastlane, Scopus look-up
Keywords: Children and adolescents; Internet-based cognitive behavioral therapy; Manualized treatment; Obsessive-compulsive disorder; Sensor technology